Evaluation of End-of-Life Vehicle Recycling in India: A Techno-Socio-Economic Analysis - Molla, Altaf Hossain; Abu Mansor, Mohd Radzi; Saibani, Nizaroyani; Hashim, Noor Azuan; Harun, Zambri (International Journal of Integrated Engineering, 2023)
In light of the rapidly advancing Indian automotive sector, the issue of end-of-life vehicles (ELVs) has emerged as a matter of significant concern. Particularly critical aspects encompass recycling procedures, environmental impacts, and social implications. With the inevitable proliferation of ELVs anticipated in the next decade, the imperative for effective and sustainable ELV management becomes paramount, necessitating a comprehensive analysis of India's burgeoning ELV recycling landscape. The present study endeavors to scrutinize India's ELV recycling system from technological, social, and economic perspectives, constituting a preliminary step toward a judicious evaluation of sustainability in ELV recycling and performing a SWOT (strengths, weaknesses, opportunities, and threats) analysis to appraise India's ELV recycling framework comprehensively. Furthermore, the ensuing recommendations shall furnish invaluable insights for the development and implementation of forthcoming regulatory and legal frameworks that adequately incorporate the economic, social, environmental, and technological aspects of ELV recycling in India. To accomplish this endeavor, the study has diligently conducted in-depth interviews with pertinent stakeholders, undertaken rigorous field investigations, and administered comprehensive surveys. Additionally, an exhaustive examination of the existing literature has been undertaken to probe the current ELV recycling system, address lingering challenges, and proffer recommendations to elevate the ELV recycling infrastructure. The outcomes of this study may assist in developing deeper comprehension of India's ELV recycling system while furnishing pragmatic recommendations to fortify its efficacy.